A capacity analysis of outdoor - backhaul network using WLAN and radio over fiber technology - Teguh Prakoso, author; Razali Ngah, author; Tharek Abdul Rahman, author; Zabih Ghassemlooy, author; IEEE International Conference on Atennas, Propagation and System (2009: Johor) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL